2013
DOI: 10.2174/0929866511320050011
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Analysis of the Conserved EFhd2 Protein

Abstract: EFhd2 is a novel protein conserved from C. elegans to H. sapiens. This novel protein was originally identified in cells of the immune and central nervous systems. However, it is most abundant in the central nervous system, where it has been found associated with pathological forms of the microtubule-associated protein tau. The physiological or pathological roles of EFhd2 are poorly understood. In this study, a functional and structural analysis was carried to characterize the molecular requirements for EFhd2’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…4b). Consistent with a previous study showing that thermostability of EFhd2 was restored by Ca 2+ at a high temperature31, the half aggregation temperature for both EF-hand mutants that bind only one Ca 2+ is significantly lower ( CD EFhd2 EF1 : 62.32 ± 0.14 °C, CD EFhd2 EF2 : 57.90 ± 0.60 °C) than the two Ca 2+ -bound EFhd2 ( CD EFhd2: 84.89 ± 0.01 °C) and is consistent with ref. 30 and 31.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…4b). Consistent with a previous study showing that thermostability of EFhd2 was restored by Ca 2+ at a high temperature31, the half aggregation temperature for both EF-hand mutants that bind only one Ca 2+ is significantly lower ( CD EFhd2 EF1 : 62.32 ± 0.14 °C, CD EFhd2 EF2 : 57.90 ± 0.60 °C) than the two Ca 2+ -bound EFhd2 ( CD EFhd2: 84.89 ± 0.01 °C) and is consistent with ref. 30 and 31.…”
Section: Resultssupporting
confidence: 93%
“…Taking into consideration a previous study and structural similarity between Ca 2+ -peptide-CaM complexes, the observations for STIM1 and CD EFhd2 support the hypothesis that high affinity for Ca 2+ and intramolecular interactions of CD EFhd2 are likely to maximise stabilisation of the EFhd2 fold. In support of this hypothesis is the thermostability results of EFhd2, which showed that the protein thermal stability at high temperature was restored by Ca 2+  31. This is further emphasised by the observation that CD EFhd2 remained stable in solution, even at high temperatures in the presence of two Ca 2+ ions (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…To date, no study has linked EFHD2 with PD. Multiple sequence alignment of EFHD2 showed that the identified phosphosite, serine 74, is highly conserved among several species (data not shown) and lies within the N-terminal region of EFHD2 that may be important for regulating calcium-binding activity (Ferrer-Acosta et al , 2013a). FKBP38 is a membrane chaperone predominantly localised in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Both proteins bind Ca 2 + . (2)(3)(4) EFhd2 is highly expressed in the brain, (5) has been proposed to be a calcium sensor protein, (3) and is putatively linked to neurodegenerative diseases (see review (1) ). EFhd1 has been shown to be involved in neuronal differentiation in a cell line model.…”
Section: Introductionmentioning
confidence: 99%